Efecto de las ventanas de nacimiento sobre la morfometría y peso de órganos linfoides en pollos COBB-500 - Zambrano Toala, Mayra Calixta (2024)
The effect of birth windows on the weight and morphometry of lymphoid organs was evaluated. 480 COBB-500 chickens were distributed in four treatments according to incubation hours: T1 486 h, T2 492 h, T3 498 h and T4 504 h, separated by sex. The study was carried out in the Teaching, Research and Linkage Unit, Incubator Plant and Hato Bovino chicken breeding shed at ESPAM MFL, the research was developed under a Completely Randomized Block Design (DBCA), with the inductive method and the Data collection was carried out with observation and recording techniques, subjected to analysis of variance (ADEVA) and comparisons of means with the 5% Tukey test. The variables evaluated were weight and morphometric index of lymphoid organs and Bursa of Fabricius/Spleen weight ratio. On the first day, T3 (females), they obtained significantly higher weights (p<0.05), while on day 21, T2 (males) the lymphoid organs Thymus, Spleen, Bursa of Fabricius were significantly heavier (p<0.05), at birth and day 21, there was no significant difference (p>0.05) with respect to the morphometric indices for Thymus and Spleen but there was for Bursa of Fabricio (p<0.05); on day 21 there was no significant difference (p>0.05) for these organs. It is concluded that there is an effect of the birth window on the weight of the chickens, weight of lymphoid organs and morphometric index on the day of birth and 21 days of life of the chickens.